2020
DOI: 10.1038/s41419-020-2416-1
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED ARTICLE: The HOTAIRM1/miR-107/TDG axis regulates papillary thyroid cancer cell proliferation and invasion

Abstract: The long noncoding RNA (lncRNA), HOX antisense intergenic RNA myeloid 1 (HOTAIRM1), has been shown to act as a tumor suppressor in various human cancers. However, the overall biological roles and clinical significance of HOTAIRM1 in papillary thyroid cancer (PTC) have not been investigated. In this study, we used quantitative reverse transcription PCR (qRT-PCR) to show that HOTAIRM1 was significantly downregulated in PTC tissues and low HOTAIRM1 expression levels were associated with lymph node metastasis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“…Subsequent studies have also confirmed that HOTAIRM1 competes with endogenous miR-107. In addition, these studies also demonstrated that HOTAIRM1 regulates the expression of TDG in a miR-107-meditated manner (47). These data indicate that HOTAIRM1 acts as a tumor suppressor gene in PTC, and may serve as a therapeutic target for PTC patients.…”
Section: Hox Antisense Intergenic Rna Myeloid 1 (Hotairm1)mentioning
confidence: 67%
See 1 more Smart Citation
“…Subsequent studies have also confirmed that HOTAIRM1 competes with endogenous miR-107. In addition, these studies also demonstrated that HOTAIRM1 regulates the expression of TDG in a miR-107-meditated manner (47). These data indicate that HOTAIRM1 acts as a tumor suppressor gene in PTC, and may serve as a therapeutic target for PTC patients.…”
Section: Hox Antisense Intergenic Rna Myeloid 1 (Hotairm1)mentioning
confidence: 67%
“…The differential expressions of those lncRNAs have also been found to be cells, tissue, and plasma in the TC. As discussed earlier, some lncRNAs, such as CCAT1, H19, HCP5, HOTTIP, , MALAT1, HOXA-AS2, SNHG15, SPRY4-IT, and UCA1, have been found to be upregulated in TC (7,23,25,26,30,42,70,111,112), whereas others, such as BANCR, AB074169, ASMTL-AS1, BLACAT1, CASC2, HOTAIRM1, GAS5, PAR5, SNHG3, GAS8-AS1, and MEG3 are downregulated (38)(39)(40)(43)(44)(45)47,104,108,112,113). This unique biologic behavior exhibited by different groups of lncRNAs shows value for the prognostic and diagnostic determination in TC patients.…”
Section: Lncrnas As Diagnostic and Prognostic Markers In Tcmentioning
confidence: 74%
“…As a kind of versatile non-coding RNA, lncRNAs have been extensively validated to function their biological role via varying mechanisms (21,22), in which functioning as ceRNA to sponge target miRNAs to disrupt the miRNAs-mediated degradation of target genes seizes great momentum (56,57) to be implicated in tumor progression and metastasis (27,61). Importantly, miRNA-mediated lncRNA/mRNA crosstalk plays an important role in the development and metastasis of thyroid cancer (28,62,63), including lymphatic metastasis (32)(33)(34). In this study, our results revealed that MAPK8IP1P2 functioned as ceRNA to sponge miR-146b-3p, which further disrupted the inhibitory effect of miR-146b-3p on NF2, RASSF1, and RASSF5 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, there is a great body of evidence reporting the role of lncRNAs in the development, progression, and metastasis in a number of cancers (27)(28)(29), including lymph node metastasis (30,31). Notably, numerous studies have shown that aberrant expression of lncRNAs is significantly correlated with lymph node metastasis in thyroid cancer patients (32)(33)(34). Although these findings indicated that lncRNAs may hold clinical applicable value as the potential predictive markers for early detection of lymph node metastasis in thyroid cancer, whether lncRNAs affects lymph node metastasis of thyroid cancer in vivo is not determined in these studies.…”
Section: Introductionmentioning
confidence: 99%
“…Lipofectamine 2000 (Thermo Fisher Scientific, MA, USA) was adopted to co-transfect pmirGLO-CXCL10-WT or pmirGLO-CXCL10-MUT with miR-503-5p mimic or miR-NC (Invitrogen) into KYSE30 and Ec109 cells. Luciferase activity was measured by a fluorometer (PerkinElmer Life Sciences, Boston, MA, USA) and dual-luciferase reporter gene detection system (Promega) [ 21 ]. The fluorescence intensity was detected with Glomax20/20 Luminometer (E5311, Promega).…”
Section: Methodsmentioning
confidence: 99%